Constitution Of India And Human Rights (Journal of Namibian Studies : History Politics Culture, 2023)
The Constitution of India, adopted on November 26, 1949, and enforced on January 26, 1950, stands as a testament to the nation's unwavering commitment to democratic principles and social justice. It is the world's longest written constitution, reflecting the immense diversity and complexity of Indian society. The preamble of the Constitution outlines the fundamental values and aspirations of the nation. It declares India as a sovereign, socialist, secular, and democratic republic. These ideals are the bedrock upon which the entire constitutional framework is built. India is an independent nation, free from external control. It has the authority to conduct its own affairs without interference from foreign powers. The Constitution aims to promote economic and social equality, ensuring that the benefits of development reach all sections of society. India is a secular state, guaranteeing religious freedom and equality to all citizens, irrespective of their faith. The Constitution establishes a democratic form of government, where power rests with the people. Citizens have the right to participate in the political process through elections and other democratic means. The Constitution guarantees fundamental rights to its citizens, including the right to equality, freedom of speech and expression, religion, assembly, and movement. These rights are essential for individual liberty and dignity.